PENGARUH ASOSIASI MEREK, PERSEPSI HARGA, DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN iPhone SECOND PADA MAHATIR STORE BIMA - BINTANG, RAHMAT; MUHAJIRIN, MUHAJIRIN; WIDAKDO, SUGENG (GANEC SWARA, 2024)
This research aims to determine the influence of Brand Association, Price Perception, and Lifestyle on the Second iPhone Purchase Decision at Mahatir Store Bima, as measured by the Partial Test (T Test) and Simultaneous Test (F Test). The population in this study is all consumers who is in the Bima City Area. The sampling technique uses the method purposive sampling with a sample size of 100 people. The research results show that: 1) Brand Association has a partial and significant influence on purchasing decisions at Mahatir Store Bima; Price perception has a partial and significant effect on purchasing decisions at Mahatir Store Bima; Lifestyle does not have a partial and significant influence on purchasing decisions at the Mahatir Bima store. 2). Brand Association, Price Perception, and Lifestyle simultaneously and significantly influence the purchase of iPhone Second HP at Mahatir Store Bima